EFFECT OF POSITION PROMOTION AND EMPLOYEE COMPETENCY ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION - Loren Dina Dasilfa; Suwignyo Widagdo; Yuniorita Indah Handayani (STIE Mandala Jember, 2022)
Human resources (HR) is one of the main driving forces that are important fororganizations/agencies because human resources are the implementers of every activity. For thisreason, a